STRATEGIES FOR TEACHING MIXED-ABILITY ADULT ENGLISH CLASSES - Sattarova D.I; Murtazayeva. D.U (TADQIQOTLAR, 2026)
Abstract Article explores effective strategies for teaching mixed-ability adult English classes, addressing the diverse needs and learning styles of adult learners. It emphasizes the importance of creating an inclusive and supportive classroom environment that fosters engagement and promotes language acquisition. The article discusses various instructional techniques, such as differentiated instruction, collaborative learning, and the use of technology, to accommodate varying proficiency levels. Additionally, it highlights the significance of assessing learners’ needs and providing personalized feedback to enhance their learning experience. By implementing these strategies, educators can effectively meet the challenges posed by mixed-ability classrooms and facilitate meaningful language learning for all students.